2003
DOI: 10.1101/gr.907603
|View full text |Cite
|
Sign up to set email alerts
|

Extrachromosomal Circular DNA of Tandemly Repeated Genomic Sequences in Drosophila

Abstract: One characteristic of genomic plasticity is the presence of extrachromosomal circular DNA (eccDNA). This DNA is found in various eukaryotes from yeast to humans, and its levels are elevated by exposure to carcinogens. eccDNA is heterogeneous in size and composed of chromosomal sequences. In this study we used two-dimensional gel electrophoresis to detect and characterize eccDNA in Drosophila. We found eccDNA throughout the fly's life cycle. These molecules comprise up to 10% of the total repetitive DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
168
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(180 citation statements)
references
References 42 publications
12
168
0
Order By: Relevance
“…Somatic elimination of repeated DNAs is not unique to flies (58), nor is it restricted to the rDNA (32,33); the extent to which it affects other repeated heterochromatic DNA is unknown (59). Lemos and colleagues recently showed polymorphisms of heterochromatic Y chromosomes, but did not map the source of those polymorphisms (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Somatic elimination of repeated DNAs is not unique to flies (58), nor is it restricted to the rDNA (32,33); the extent to which it affects other repeated heterochromatic DNA is unknown (59). Lemos and colleagues recently showed polymorphisms of heterochromatic Y chromosomes, but did not map the source of those polymorphisms (6).…”
Section: Discussionmentioning
confidence: 99%
“…As a cell divides and approaches terminal differentiation, rDNA is lost and this milieu changes. Loss could occur through recombination or damage leading to extrachromosomal acentric rDNA circles (33) or through unequal sister chromatid exchange (39,47). Cells which lose rDNA early in their lineage pass a threshold, lose some heterochromatin forming potential, and allow activation of silenced genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to identify recombination proteins required for ecc DNA formation in Drosophila have been unsuccessful 22 and Drosophila RAD52 homologues have not been identified. A recent study identified Ligase IV, an essential regulator of NHEJ, as necessary for ecc DNA formation in mammals 23 .…”
Section: Ligase 4 Mutations Partially Suppress the Su(var)3-9 Multiplmentioning
confidence: 99%